Heat and mass transfer studies in liquefied petroleum gas storage operations - Mat, Hanapi; Zakaria, Zainal; Yusoff, Zulkarnain (Faculty of Chemical and Natural Resources Engineering, 2006)
Liquefied petroleum gases (LPG) are substances such as propane and butane, which are transported and stored in the liquid phase in tanks under sufficiently high pressure. It is generated as a by-product either of oil and gas production or refining. The composition components of LPG are much simpler than that of gasoline. LPG is thought to be a cleaner fuel because it is has less impact on air quality. The objective of this thesis is to obtain detailed understanding of LPG cylinder system behavior during the continuous exhaustion or natural evaporation process via modification of the existing cylinder design. Experiments have been conducted to predict the parameters affecting the evaporation process such as surrounding temperature, pressure, composition and flowrate of LPG in cylinder based on the rig set up. The investigation of these parameters during discharging process is the initial step in a usage management of LPG, which is an essential part to evaluate the left over problem. In a parallel effort, a computer model has been developed based on the unsteady state of heat and mass transfer concepts using MATCAB 2000.